Management of Synchronous Locally Advanced Carcinoma Tongue and Early-Stage Carcinoma Esophagus in a Tertiary Cancer Center: A Rare Case Report - Nagarajan, Aswin; Sakthivelu, Arun; Ganesharajah, Selvaluxmy (Indian Journal of Medical and Paediatric Oncology, 2020)
Synchronous malignancy of tongue and esophagus is difficult to diagnose and treat since both the malignancies are aggressive and have poor survival. We report an unusual case study of locally advanced carcinoma tongue (Stage IVA) with early-stage carcinoma esophagus (Stage II) in a 43-year-old male for whom both the malignancies were treated with concurrent chemoradiation in a sequential manner and the patient had a complete response of both malignancies without much treatment-related morbidity and the patient is coming for follow-up with the disease-free survival of 6 months.
Keywords: Carcinoma esophagus; carcinoma tongue; early-stage; locally advanced; synchronous